Blake's Spiritual JOurney in the little boy lost and the little boy found by william shakespear - Indratwuri, Rena (LANTERN (Journal on English Language, Culture and Literature), 2013)
Poem is a type of prose which is one of literature genres besides novel and drama. Unlike novel or drama, poem is one of way to express the poet feeling. There are a lot of poets that create a poem with various kinds of theme but they still use their own style. The readers can imagine the story in the poet’s mind through the story presented in it. The readers give response to the imaginary experience in the poem as a pleasing experience. This response makes the writer more interested to poem than other genres. Besides, poem can entertain the readers, it also teaches us about the value of life.